Isolation and Identification of Hydrocarbon Degradation Bacteria and Phosphate Solubilizing Bacteria in Oil Contaminated Soil in Bojonegoro, East Java, Indonesia - Rahayu, Yuni Sri (Universitas Pendidikan Indonesia, 2019)
Petroleum is a mixture of hydrocarbon complexes with organic compounds from sulfur, oxygen, nitrogen and metal-containing compounds. These organic compounds can be used as substrate for bacterial growth. This study aimed to isolate and identify hydrocarbon degrading bacteria and phosphate solubilizing bacteria in oil-contaminated soil in Bojonegoro. This study used an exploration method to find each of the two types of hydrocarbon degrading bacteria and phosphate solubilizing bacteria from soil samples in Bojonegoro that contaminated by oil. Identification of isolates bacterial included macroscopic observations of bacteria, gram staining on bacterial cells and physiological tests. Macroscopic observations include the form of colonies, colony diameter, colony color, colony edge, and elevation. The physiological test using Microbact Identification System to determine the physiological characteristics of bacteria so that genera and types of bacteria can be known. The identification of organisms was based on changes in pH and use of the substrate. The results of data analysis were obtained from five types of bacteria from soil samples that contaminated by oil which were successfully isolated. After identification of species was done, four species of bacteria were obtained, namely Pseudomonas pseudomallei, Pseudomonas fluorescens-25, Flavobacterium odoratum, and Enterococcus sp.